A Cooperative Spectrum Sensing Method of Aeronautical Radio Based on Reputation - Yufeng Li; Nairui Hu; Yupeng Wang (Dianxin kexue)
The traditional cooperative spectrum sensing algorithm of aeronautical radio can't distinguish the node type（normal/malicious）, though weighted sequential probability ratio test（WSPRT）method meets the requirement but when the spectrum sensing data falsification（SSDF）node is exist, it can't keep high sensing accuracy any more. An improved WSPRT was proposed. On the foundation of traditional WSPRT, reputation rewards and punishment algorithm was improved, and sensing stability factor was taken into account. The simulation results show that it can make identify malicious cognitive nodes easier and make the fusion algorithm distinguish malicious user more accurate.